The use of english songs on pronunciation acquisition of english as a foreing lenguage, applied to students from bachelor degrees at Universidad de Costa Rica to correct their most common mistakes as spanish speakers = El uso de canciones en inglés para la adquisición de pronunciación del inglés como lengua extranjera, aplicado a estudiantes de bachillerato de la Universidad de Costa Rica para corregir sus errores más comunes como hispanohablantes - Borge Obando, Ileana Vanesa (2022)
The following qualitative research states the use of songs in English as a didactic strategy in order to foster pronunciation by determining the most common mistakes that Spanish speakers make. Also, it exposes the participants' perception on the specific songs chosen and the effectiveness of its use. As well, it explores the application of the Participatory Action Research method to conduct the study of pronunciation acquisition and its role in the students' intelligibility. Finally, it defines different types of limitations and recommendations for future research on the "Mother Tongue Effect", which was the most common type of mistake that students made.